2010
DOI: 10.1007/s10875-010-9457-7
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus casei reduces the Inflammatory Joint Damage Associated with Collagen-Induced Arthritis (CIA) by Reducing the Pro-Inflammatory Cytokines

Abstract: This study evaluated the therapeutic efficacy of Lactobacillus casei in treating rheumatoid arthritis using collagen-induced arthritis (CIA) animal model. Healthy female Wistar rats (weight-180-200 g) were included in this study. Oral administration of L. casei was started on the same day. Indomethacin was used as standard reference drug. Serum level of IL-6, α-TNF, and IL-10 were observed. Four-point arthritis indexes were also assessed at the end of week for 28th day. L. casei-treated rats had shown normal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(99 citation statements)
references
References 36 publications
5
91
0
3
Order By: Relevance
“…These findings suggested that inhibition of COX-2 may be another mechanism to suppress the development of 4NQO-induced oral carcinogenesis. Several species of probiotics were also proven to reduce the inflammation response by downregulating the COX-2 expression in vivo (36,37). However, this mechanism had not been proven effective in cancer prevention.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that inhibition of COX-2 may be another mechanism to suppress the development of 4NQO-induced oral carcinogenesis. Several species of probiotics were also proven to reduce the inflammation response by downregulating the COX-2 expression in vivo (36,37). However, this mechanism had not been proven effective in cancer prevention.…”
Section: Discussionmentioning
confidence: 99%
“…8 Lactobacillus casei is usually used in dietary supplements, and previous studies have shown that L. casei possesses strong anti-inflammatory activity. [10][11][12][13][14] In collagen-induced arthritis (CIA) animal model, oral administration of L. casei significantly decreased the serum levels of pro-inflammatory cytokines IL-6 and TNF-α and increased the levels of IL-10.…”
Section: Wang Et Almentioning
confidence: 99%
“…Dieleman et al in a study of transgenic rats, which were free of HLA-B27, showed that the oral provision of probiotics species Lactobacillus rhamnosus GG (LGG) could partially prevent the relapse of colitis. In addition to the above, another study demonstrated that probiotics, such as, Lactobacillus casei has strong anti -inflammatory and antiarthritic effect on collagen -induced arthritis rat model 54 . Also, in one pilot study, patients with active SpA and quiescent ulcerative colitis, consumed probiotics (Lactobacillus acidophilus and Lactobacillus salivarius), and the result showed that there was a significant reduction of Visual Analogue Scale Score and Bath AS Disease Activity Index (BASDAI) 55 .…”
Section: Probiotics And/or Prebiotics As Therapeutic Treatment Of Asmentioning
confidence: 89%